2018
DOI: 10.1002/srin.201800112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vanadium on the Phase Transformation Behavior of Ti–Mo Microalloyed Ultra‐High Strength Steel

Abstract: Vanadium is a vital microalloying element in the precipitation hardening of hot‐rolled high strength steel. Its effects on the continuous cooling phase transformation behavior, microstructure, and properties of Ti–Mo and Ti–Mo–V microalloyed ultra‐high strength steels are studied by the thermal simulator, scanning electron microscopy (SEM), high‐resolution transmission electron microscopy (HRTEM), energy dispersive spectrometer (EDS), and electron backscatter diffractometer (EBSD). The dynamic continuous cooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…It has been confirmed in various studies [23,24,28] that with an increasing vanadium content, the rate of perlite transformation slows and the steel hardness increases by increasing the vanadium content. Vanadium in solution seems to affect the mobility of the carbon atoms [10,[25][26][27][28][29][30]. Using Thermo-Calc software we performed the thermodynamic analysis, showing that the type of stable carbides in the matrix changes from cementite to M6C and M7C3 carbides.…”
Section: Microstructural Evolution and Transformation Kineticsmentioning
confidence: 80%
See 2 more Smart Citations
“…It has been confirmed in various studies [23,24,28] that with an increasing vanadium content, the rate of perlite transformation slows and the steel hardness increases by increasing the vanadium content. Vanadium in solution seems to affect the mobility of the carbon atoms [10,[25][26][27][28][29][30]. Using Thermo-Calc software we performed the thermodynamic analysis, showing that the type of stable carbides in the matrix changes from cementite to M6C and M7C3 carbides.…”
Section: Microstructural Evolution and Transformation Kineticsmentioning
confidence: 80%
“…However, because of the formation of carbide in the sample containing cerium and lanthanum in the bainite transformation, the carbon content of the parent phase has decreased, and as a result, its thermodynamic stability has decreased and martensitic transformation occurred at higher temperatures than the vanadium containing sample. It has been confirmed in various studies [23,24,28] that with an increasing vanadium content, the rate of perlite transformation slows and the steel hardness increases by increasing the vanadium content. Vanadium in solution seems to affect the mobility of the carbon atoms [10,[25][26][27][28][29][30].…”
Section: Microstructural Evolution and Transformation Kineticsmentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, the literature [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ] reported that adding Nb or V to Ti−Mo steel could further optimize microstructures and improve mechanical properties. Cai et al [ 10 ] improved the yield strength of ultra-low carbon Ti−Mo steel to 680 MPa by adding Nb.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the addition of Nb could also refine ferrite grains and inhibit bainitic transformation, thus improving the mechanical properties of hot-rolled ferritic steel. Compared to Nb, V could also inhibit bainitic transformation and has a stronger ability for precipitation strengthening [ 14 ]. Zhang et al [ 15 ] reported that Ti−Mo−V composite microalloying could improve the yield strength of ferritic steel to 900 MPa due to the contribution of nano-sized (Ti, Mo, V)C particles.…”
Section: Introductionmentioning
confidence: 99%